Smart damping of geometrically nonlinear vibrations of functionally graded sandwich plates using 1–3 piezoelectric composites. Issue 6 (2nd June 2016) - Kumar, R. Suresh; Ray, M. C.
ABSTRACT: Geometrically nonlinear dynamic analysis of smart functionally graded (FG) sandwich plates integrated with the patches of active constrained layer damping (ACLD) treatment has been carried out by the finite element method. The constraining layer of the ACLD treatment is considered to be made of vertically/obliquely reinforced 1–3 piezoelectric composite while the constrained layer is made of a viscoelastic material, which is modeled using the Golla–Hughes–McTavish method in the time domain. The top and bottom faces of the substrate sandwich plate are composed of the FG isotropic material whose mechanical properties are assumed to vary according to a standard power-law distribution in terms of the volume fractions of the constituents while the core layer may be either a soft honeycomb material or a hard ceramic material. Several FG sandwich plates with different core configurations are studied to evaluate the numerical results. The numerical results indicate that the ACLD patches significantly improve the damping characteristics of the FG sandwich plates for suppressing their geometrically nonlinear vibrations. Effects of metal- or ceramic-rich top and bottom surfaces, the variation of power-law index on the control authority of the ACLD patches have been investigated. Emphasis has also been placed on investigating the effect of the variation of piezoelectric fiber orientation angle on the performance of the ACLD patches.